Comparative clinical study of the effectiveness of different dental bleaching methods - two year follow-up - Rafael Francisco Lia Mondelli; Juliana Felipi David e Góes de Azevedo; Ana Carolina Francisconi; Cristiane Machado de Almeida; Sérgio Kiyoshi Ishikiriama (University of São Paulo, 2012)
This study evaluated color change, stability, and tooth sensitivity in patients submitted to different bleaching techniques. MATERIAL AND METHODS: In this study, 48 patients were divided into five groups. A half-mouth design was conducted to compare two in-office bleaching techniques (with and without light activation): G1: 35% hydrogen peroxide (HP) (Lase Peroxide - DMC Equipments, São Carlos, SP, Brazil) + hybrid light (HL) (LED/Diode Laser, Whitening Lase II DMC Equipments, São Carlos, SP, Brazil); G2: 35% HP; G3: 38% HP (X-traBoost - Ultradent, South Jordan UT, USA) + HL; G4: 38% HP; and G5: 15% carbamide peroxide (CP) (Opalescence PF - Ultradent, South Jordan UT, USA). For G1 and G3, HP was applied on the enamel surface for 3 consecutive applications activated by HL. Each application included 3x3' HL activations with 1' between each interval; for G2 and G4, HP was applied 3x15' with 15' between intervals; and for G5, 15% CP was applied for 120'/10 days at home. A spectrophotometer was used to measure color change before the treatment and after 24 h, 1 week, 1, 6, 12, 18 and 24 months. A VAS questionnaire was used to evaluate tooth sensitivity before the treatment, immediately following treatment, 24 h after and finally 1 week after. RESULTS: Statistical analysis did not reveal any significant differences between in-office bleaching with or without HL activation related to effectiveness; nevertheless the time required was less with HL. Statistical differences were observed between the results after 24 h, 1 week and 1, 6, 12, 18 and 24 months (intergroup). Immediately, in-office bleaching increased tooth sensitivity. The groups activated with HL required less application time with gel. CONCLUSION: All techniques and bleaching agents used were effective and demonstrated similar behaviors.